MODEL ARSITEKTUR POHON FAMILI DIPTEROCARPACEAE DI KEBUN RAYA SAMBAS KABUPATEN SAMBAS - Erlin, Erlin; Sisillia, Lolyta; Manurung, Togar Fernando (Universitas Tanjungpura, 2023)
Sambas Botanical Garden functions as a conservation area that has a fairly high diversity of plants with vegetation that is dominated by Dipterocarpaceae family. Research on architectural models of the Dipterocarpaceae family in the Sambas Botanical Garden needs to be carried out to obtain a database of the diversity of architectural models of the Dipterocarpaceae trees that grow in the Sambas Botanical Garden. It was also to provide complete data related to the architectural model which is expected to be used as a reference in the management of the Sambas Botanical Garden. The purpose of this study was to determine the architectural model of the Dipterocarpaceae family tree. The benefit of the research was to provide a source of information regarding the description of the architectural model of the Dipterocarpaceae family tree that grows in the Sambas Botanical Garden. This research was conducted using survey methods, data collection was carried out by roaming, namely by exploring every corner of the location in the Sambas Botanical Gardens. The results of this study found 5 architectural models of 28 species of trees in the Dipterocarpaceae family, namely the Roux model, Massart model, Scarrone model, Rauh model, and Attims model. The Roux model is the most common tree architectural model, with 14 species.Keywords: Dipterocarpaceae, Sambas Botanical Garden, Tree architecture.AbstrakKebun Raya Sambas difungsikan sebagai kawasan konservasi yang memiliki keanekaragaman tumbuhan yang cukup tinggi dengan vegetasi yang mendominasi yaitu dari famili Dipterocarpaceae. Penelitian tentang model arsitektur pohon famili Dipterocarpaceae di Kebun Raya Sambas perlu dilakukan untuk mendapatkan database keanekaragaman model arsitektur pohon famili Dipterocarpaceae yang tumbuh di Kebun Raya Sambas. Selain itu memberikan data secara lengkap terkait model arsitektur yang diharapkan dapat dijadikan sebagai acuan dalam pengelolaan Kebun Raya Sambas. Tujuan dari penelitian ini adalah menentukan model arsitektur pohon famili Dipterocarpaceae. Manfaat penelitian yaitu dapat memberikan sumber informasi deskripsi model arsitektur pohon famili Dipterocarpaceae yang tumbuh di Kebun Raya Sambas. Penelitian ini menggunakan metode survey, pengumpulan data dilakukan dengan cara jelajah, yaitu dengan menjelajahi setiap sudut lokasi di Kebun Raya Sambas. Hasil penelitian ini ditemukan 5 model arsitektur dari 28 spesies pohon famili Dipterocarpaceae yaitu model Roux, model Massart, model Scarrone, model Rauh, dan model Attims. Model Roux merupakan model arsitektur pohon yang paling banyak dijumpai yaitu sebanyak 14 spesies.Kata kunci: Dipterocarpaceae, Kebun Raya Sambas, Arsitektur Pohon.